Neuroimmune Responses Mediate Depression-Related Behaviors following Acute Colitis - Vinicius M. Gadotti; Graciela Andonegui; Zizhen Zhang; Said M'Dahoma; Cristiane H. Baggio; Lina Chen; Lilian Basso; Christophe Altier; Wallace K. MacNaughton; Paul Kubes; Gerald W. Zamponi (iScience, 2019)
Summary: Many patients with visceral inflammation develop pain and psychiatric comorbidities such as major depressive disorder, worsening the quality of life and increasing the risk of suicide. Here we show that neuroimmune activation in mice with dextran sodium sulfate-induced colitis is accompanied by the development of pain and depressive behaviors. Importantly, treatment with the flavonoid luteolin prevented both neuroimmune responses and behavioral abnormalities, suggesting a new potential therapeutic approach for patients with inflammatory bowel diseases. : Pathophysiology; Behavioral Neuroscience; Cellular Neuroscience; Immunity Subject Areas: Pathophysiology, Behavioral Neuroscience, Cellular Neuroscience, Immunity